Teacher Effectiveness: “A Comparative study of Assistant Professors” - Rekha Bawa, Prof. Kavita Varma (International Journal of Advanced Science and Technology, 2020)
This study is conducted to find out the gender differentiation in reference to teacher effectiveness of Assistant professors of GLA University, Mathura. Descriptive survey method was used. Male and Female Assistant professors were selected through a convenience sampling method and 50 male assistant professors and 50 female assistant professors from all streams selected through a simple random method. Data was collected by using Umme Kulsum’s scale of Teacher Effectiveness .Mean score, Standard Deviation (S.D) and t- test were used to draw the conclusions. Differences between teacher effectiveness of female and male assistant professors of the University found insignificant.